The role of vitamin D in selected autoimmune diseases - Aleksandra Wiśniewska; Alicja Szypowska (National Institute of Public Health - National Institute of Hygiene, 2021)
The authors of recently published scientific papers are focusing increasingly often on the effect of vitamin D on immune processes. In the case of deficiencies of this vitamin, an imbalance in the immune system is observed, which is associated with the intensification of the inflammatory reaction in the body and the increased possibility of an autoimmune reaction. Therefore, due to the growing interest of scientists in the relationship between the effects of vitamin D and the development of autoimmune diseases, this paper considers the use of Vitamin D in autoimmune therapies. However, the mechanism of vitamin D on individual autoimmune diseases has not been elucidated so far, therefore there is a need for further research. The importance of maintaining normal plasma vitamin D levels to reduce the risk of developing autoimmune diseases has been demonstrated by the authors of other studies. They showed that vitamin D levels influenced the course, severity of symptoms and frequency of relapses of autoimmune thyroid disease, inflammatory bowel disease, and rheumatoid arthritis.